2015
DOI: 10.1007/s10646-015-1499-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heavy metals mobility and toxicity in contaminated sediments by sequential extraction and a battery of bioassays

Abstract: The aim of this study was to assess heavy metals mobility and toxicity in sediments collected from a dam reservoir in the conditions of intensive human impact by using chemical fractionation and a battery of bioassays. In the studies, the test organisms were exposed to substances dissolved in water (Microtox, Phytotestkit) as well to substances absorbed on the surface of solid particles (Phytotoxkit, Ostracodtoxkit F). The studies showed that sediments from the Rybnik reservoir are toxic, but the tested organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
87
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 44 publications
(77 reference statements)
6
87
1
2
Order By: Relevance
“…For each of the plants, the mean value of the germination index indicated the dominance of the inhibitory effect of the tested sediment on plant growth. Baran & Tarnawski (2015) who reported that S. saccharatum is the most sensitive species for identifying phytotoxic sediment samples compared to L. sativum and S. alba. Among dicotyledonous plants, S. alba turned out to be a more sensitive one since up to 73% of the sediment samples were observed to inhibit its growth.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For each of the plants, the mean value of the germination index indicated the dominance of the inhibitory effect of the tested sediment on plant growth. Baran & Tarnawski (2015) who reported that S. saccharatum is the most sensitive species for identifying phytotoxic sediment samples compared to L. sativum and S. alba. Among dicotyledonous plants, S. alba turned out to be a more sensitive one since up to 73% of the sediment samples were observed to inhibit its growth.…”
Section: Resultsmentioning
confidence: 99%
“…Low or no toxicity of sediments from heavy metals may be caused i.a. by their presence in a very stable and insoluble form, a high content of organic matter or clay fraction as well as a neutral or a slightly alkaline reaction (Baran & Tarnawski 2013, 2015. The studies conducted by Gong et al (2001) and Czerniawska-Kusza et al (2006) also confirmed that the false assessment may be caused by sediments rich in organic matter, which can hide the inhibitory effect of pollutants on test plants.…”
Section: Fig 2 Spatial Distribution Phytotoxicity (Gi) Of Bottom Sementioning
confidence: 94%
See 2 more Smart Citations
“…The occurrence of metals in sediments is extremely important from an ecological point of view, because some metals are toxic (Pb, Cd, Hg), and all in excess are harmful to living organisms (Baran and Tarnawski, 2013;. An important feature which distinguishes metals from other undesirable substances is the fact that they do not undergo biodegradation but only biotransformation (Singh et al, 2005;Yuvanatemiya and Boyd, 2006;Rabajczyk, 2011;Baran and Tarnawski, 2015). Metals may be immobilized in the sediments for a long time, but in variable atmospheric conditions they may be easily leached from the sediments and pose a hazard of returning the element to cycling in nature (Rabajczyk, 2011;Baran et al, 2011;Baran and Tarnawski, 2013).…”
Section: Introductionmentioning
confidence: 99%